Retrospective seroepidemiological investigations against Morbillivirus, Toxoplasma gondii and Brucella spp. in cetaceans stranded along the Italian coastline (1998-2014) - Profeta, Francesca; Di Francesco, Cristina Esmeralda; Marsilio, Fulvio; Mignone, Walter; Di Nocera, Fabio; De Carlo, Esterina; Lucifora, Giuseppe; Pietroluongo, Guido; Baffoni, Marina; Cocumelli, Cristiano; Eleni, Claudia; Terracciano, Giuliana; et al. (Research in Veterinary Science, 2015)
This study reports the results of seroepidemiological investigations carried out against Morbillivirus, Toxoplasma gondll and Brucella spp. on blood serum samples collected from 70 cetacean specimens found stranded along the Italian coastline between 1998 and 2014. A total number of 23 serum samples (32.8%) obtained from Stenella coeruleoalba, Tursiops truncatus, Balaenoptera physalus and Globicephala melas harboured anti-Morbillivirus neutralizing antibodies. Ten sera (16%) collected from S. coeruleoalba and T. truncatus were found positive against T. gondii, while no antibodies against Brucella spp. were found. These data reveal that stranded cetaceans provide a unique opportunity for monitoring the health status of free-ranging animals living in the Mediterranean Sea, in order to investigate the level of exposure of cetacean populations to selected infectious agents representing a serious threat for aquatic mammals.